Some factors affecting the body weights at birth, weaning and born nine months in Cyprus, local goats and their crosses - مناتي, أحمد عبد الرضا; ابراهيم سعيد, سعد; علي طه, صادق (Journal of Kerbala for Agricultural Sciences, 2015)
This study was conducted in the station for ruminant research of the State Board for Agriculture Research, Ministry of Agricultural, for the period from 01/10/2012 up to 10/02/2014 for one a production season (2013), while the previous season data were obtained from the records. The study included 447 records of 104 Local kids, 249 Cyprus kids, 68 cross1 kids (½Cyprus + ½ Local * ½ Cyprus + ½ Local) and 26 cross 2 kids (Male Local * Female Cyprus) for weights at three ages (birth, weaning, 9 months). high-significant effect (P <0.01) for each of the genetic group and birth type and month - year of birth and the age of the mother at birth and significant effect (P <0.05) for the sex of the kid and no significant effect of genetic group * sex and sex * birth type on the type Birth Weight , high significant effect (P <0.01) for the month - year of birth and the regression on the age of weaning , and significant effect (P <0.05) for the type of birth and no significant effect of both genetic group and sex and age of the mother at birth and genetic Group * sex , sex* birth type and the regression on the birth weight at weaning weight , high significant effect (P <0.01) of the regression on the weight of weaning and no significant effect of genetic group and sex and birth type and month - year of birth and the age of the mother at birth and genetic Group * sex and sex * type of birth and the regression at the age of nine months on the weight of nine months. The study aimed to determine the impact of some factors on the weight kids in goats.